[(μ‐C){Re(CO)2(η‐C5H5)}2]: A Surprisingly Simple Bimetallic Carbido Complex1. Issue 13 (19th February 2013) - Young, Rowan D.; Hill, Anthony F.; Cavigliasso, Germán E.; Stranger, Robert
<x xml:space="preserve">Abstract</x> It's easy to C: The reaction of [Re(CO)2(CS)(η‐C5H5)] with [Re(CO)2(thf)(η‐C5H5)] affords the disulfur complex [Re(CO)2(η2‐S2)(η‐C5H5)] and the remarkably simple μ‐carbido complex [(μ‐C){Re(CO)2(η‐C5H5)}2], which has been structurally characterized and computationally investigated (see picture; black C, white H, red O, green Re).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>